Numerical Modeling of Equiaxed Structure Forming in the Cast during Alloy Solidification. (2016) - Gawronska, Elzbieta; Sczygiol, Norbert; Dubow, Eugeniusz
Abstract: In this study, we assumed that only the equiaxed structure created in the cast and the characteristic dimension is the final radius of grain. Because of the difference between the initial temperature of the molten metal and of the mold, there are significant differences in the average cooling rate when the liquidus temperature is achieved. The cooling rates vary within the range of 0.78 K.s -1 to 29.88 K.s -1 . Since the average radius of grain is a function of the cooling rate, the radii of the smallest grains are 17.71 m, while the radii of the biggest grains are 366.22 m.